2013
DOI: 10.1155/2013/413980
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic Reconstruction of Current Dipoles and Quadrupoles in Three-Dimensional Space

Abstract: This paper presents an algebraic method for an inverse source problem for the Poisson equation where the source consists of dipoles and quadrupoles. This source model is significant in the magnetoencephalography inverse problem. The proposed method identifies the source parameters directly and algebraically using data without requiring an initial parameter estimate or iterative computation of the forward solution. The obtained parameters could be used for the initial solution in an optimization-based algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Multipolar source models are expected to have a major impact in the solution of the E/MEG inverse problem (IP). In this direction, several approaches have been presented in the MEG literature exploiting the availability of analytical formulas for spherical head models [10], [45], [46]. Using a single shell spherical head representation, Jerbi et al showed that source estimation errors were consistently lowered by the addition of the quadrupolar term to the standard dipole [10].…”
Section: Discussionmentioning
confidence: 99%
“…Multipolar source models are expected to have a major impact in the solution of the E/MEG inverse problem (IP). In this direction, several approaches have been presented in the MEG literature exploiting the availability of analytical formulas for spherical head models [10], [45], [46]. Using a single shell spherical head representation, Jerbi et al showed that source estimation errors were consistently lowered by the addition of the quadrupolar term to the standard dipole [10].…”
Section: Discussionmentioning
confidence: 99%